Preliminary study on microplastic abundance in mangrove sediment cores at Mae Klong River, upper Gulf of Thailand - Chaisanguansuk, Pattraporn; Phantuwongraj, Sumet; Jirapinyakul, Akkaneewut; Assawincharoenkij, Thitiphan (Frontiers in Environmental Science, 2023)
Microplastics have polluted our environment, particularly mangrove ecosystems, the barriers between land and sea that trap sediments and pollutants. The abundance of microplastics has increased in microplastic deposition and is expected to rise in the future. In this study, mangrove sediment cores were collected from the Mae Klong River mouth and Queen Sirikit Park (shoreline), Samut Songkhram province. The microplastics were analyzed using a modified flotation method, then recasted and removed organic matter. Fiber microplastics is composed of 92% and 82% of the total microplastics that found in the Mae Klong River mouth and Queen Sirikit Park, respectively. There were significant changes in the abundance of microplastics in relation to the sediment particle size (p < 0.05). The difference in location between the Queen Sirikit Park and Mae Klong River mouth sites was significant (p < 0.01). The accumulation of microplastics in the sediments was influenced by grain size and location. The polymer types of microplastics were those normally used in textiles, indicating human activity. Moreover, micro-Fourier transform infrared (µ-FTIR) spectroscopy analysis identified compounds of other small particles, including tire rubber, pigment, paint, dyes, and flame retardant. These results imply that microplastics and microparticles have polluted the mangrove sediment in the Mae Klong River basin, which is an important fishery area in the upper Gulf of Thailand.